Global engagement and returns volatility - Girma, Sourafel; Lancheros, Sandra; Riaño, Alejandro (Wiley, 2016)
This paper finds that a greater reliance on foreign market sales increases the volatility of firms’ stock returns using high-frequency data for publicly-listed Japanese manufacturing firms over the period 2000 to 2010. The two margins of global engagement we consider, namely, exports and sales via foreign affiliates (horizontal FDI), have both a positive and economically significant effect on firm-level volatility. We find, however, that increasing the intensity of sales through foreign affiliates has a stronger effect on volatility than a similar change in export intensity. We also uncover evidence consistent with the notion that firms’ need to use external finance to cover the substantial costs involved in reaching foreign consumers can be an important channel through which firms’ participation in international markets increases their exposure to economic uncertainty.